IMPROVEMENT OF THE TECHNOLOGY OF RESTRUCTURED FROZEN SEMI-FINISHED MEAT (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2026)
The innovative focus of scientific research on the technologies of meat semi-finished products is aimed at the need to develop a technological process for the production of restructured meat products, which allows to regulate the organoleptic and structural-mechanical properties of meat products, to involve in production low-grade raw materials with low functional and technological properties, to expand the assortment, to increase the yield of finished products and the profitability of production. Traditionally, in the technologies of restructured meat products, the monolithic formation of the product is achieved mainly with the help of heat treatment. One of the promising technological solutions in this direction is the development of frozen restructured semi-finished products that imitate portioned semi-finished products. The article is about research devoted to the improvement of the technology for the production of frozen restructured meat semi-finished products due to the use of restructuring mixtures in their composition. After summarizing the results of experimental research and technological development, the technology of restructured semi-finished products with the use of restructuring mixtures in their composition was substantiated, and their main quality and safety indicators were investigated. It has been proven that the quality and safety indicators of restructured frozen semi-finished meat products confirm the compliance of the products with the requirements of regulatory documentation. During the study, 19 amino acids were identified and quantified, of which 37.7% (control) and 37.1% (restructured frozen semi-finished meat products) are essential, and the remaining 62.3% (control) and 62.9% (restructured frozen semi-finished meat products) on substitute amino acids. The ratio of essential and replaceable amino acids in the control is 1:1.6, in semi-finished restructured frozen meat products – 1:1.7, which makes it possible to characterize them as products with high biological value. Thus, the implementation of the developed technology will be aimed at ensuring the quality and safety of meat semi-finished products, meeting consumer requirements regarding the taste and nutritional characteristics of the product, increasing production efficiency and forming food safety.
Keywords: restructured frozen semi-finished meat products; functional mixtures; quality and safety indicators